Metabolic memory in gestational diabetes enhances SARS-CoV-2 susceptibility in postpartum women: a prospective cohort study integrated with longitudinal metabolomics - Zhangyan Li; Qiuhan Lu; Rui Zhang; Nuerbiya Xilifu; Yue Li; Xinmei Huang; Jiaying Zhang; Shufei Zang; Guozhi Jiang; Jun Liu (Endocrine Connections)
Objective: Women with gestational diabetes mellitus (GDM) often develop a metabolic memory that increases the risk of future metabolic disorders, even after blood glucose levels normalize following clinical intervention. However, the impact of this metabolic memory on susceptibility to SARS-CoV-2 remains unclear. Therefore, we aim to investigate the potential association between metabolic memory in GDM and susceptibility to SARS-CoV-2 infection. Methods: We conducted a prospective cohort study with 1,675 pregnant women, including 197 (11.8%) with GDM. Postpartum SARS-CoV-2 infections were tracked via telephone follow-up and categorized into negative and positive groups. Logistic regression was used to explore risk factors for SARS-CoV-2 infection. Peripheral blood samples were collected from 30 GDM and 30 normal glucose-tolerant (NGT) pregnant women in three trimesters (T1, T2 and T3) for longitudinal untargeted metabolomics to identify GDM and SARS-CoV-2-associated metabolites. Limma package was applied to find differential expressed metabolites associated with SARS-CoV-2 infection and GDM. Results: Among 1,675 women, 1,348 (80.5%) tested positive for SARS-CoV-2. GDM postpartum women had higher SARS-CoV-2 infection rates (88.3 vs 79.4%, P = 0.003) than NGT women. GDM was associated with SARS-CoV-2 infection (T2: OR (95% CI): 2.17 (1.26–3.54), P = 0.005; T3: OR (95% CI): 1.70 (1.03–2.82), P = 0.040). Compared to the SARS-CoV-2 negative group, the positive group exhibited elevated levels of allantoic acid, LPE (0:0/22:6), LPC (15:0/0:0) and 1-linoleoyl-sn-glycero-3-phosphorylcholine in T1 and T2, before clinical intervention. In T3, allantoic acid remained elevated post-intervention. A similar increase as described above was observed in the GDM compared to the NGT group. The tricarboxylic acid cycle was the sole overlapping enriched pathway in the SARS-CoV-2 positive versus negative group and the GDM versus NGT group. Cis-aconitic acid, a metabolite from this pathway, was elevated in T3 in the GDM group. Conclusion: Compared to NGT, women with GDM are at a higher risk of postnatal SARS-CoV-2 infection. Metabolic memory from GDM may heighten susceptibility to SARS-CoV-2.